Arbitrary States Social Control and Modern Authoritarianism in Museveni's Uganda - Tapscott, Rebecca (Oxford University Press, 2021)
In recent years, scholars of authoritarianism have noted a trend in which institutions designed to check arbitrary power have been hollowed out to facilitate its exercise. As they grapple with how to understand the disjunct between state institutions and enforcement power, scholars of sub-Saharan African states have been doing so for decades. Based on in-depth field research on local security in Museveni's Uganda, Tapscott offers an innovative and provocative contribution to studies of authoritarianism and state consolidation: rulers maintain control by creating unpredictability in the everyday lives of local authorities and ordinary citizens. In this type of modern authoritarian regime, rulers institutionalize arbitrariness to limit the space for political action, while they keep citizens marginally engaged in the democratic process. By showing not just that unpredictability matters for governance, but also how it is manufactured and sustained, this book challenges and extends cutting-edge scholarship on authoritarianism, the state, and governance.